Stigma in Malay Patients with HIV/AIDS in Malaysia - Fadzil, Nor Asyikin; Othman, Zahiruddin; Mustafa, Mahiran (Japan International Cultural Exchange Foundation, 2016)
Background: Previous study noted severe impairment of social well-being, compared to other area of QoL in HIV patients, suggesting the role of moral and religious values concerning HIV infection. Objectives: The objective of this study was to evaluate the level and correlates of HIV-related stigma experienced by the patients. Methods: A total of 100 consenting Malay Muslim HIV patients attending the infectious disease out-patient clinic, Hospital Raja Perempuan Zainab II from July 2012 to February 2013 were recruited for study. Results: (1) Stigma among HIV patients attending out-patient clinic was high, particularly disclosure concerns; (2) Female HIV patients had significantly higher disclosure concerns compared to male HIV patients; (3) Among the studied variables, only disclosure was independently associated with total stigma. Conclusion: HIV-related stigma was high and significantly correlated with disclosure of HIV status among Malay Muslim HIV patients. Further studies are warranted to determine additional factors, such as culture and religiosity, which may influence the stigma.